A Nonseminomatous Germ Cell Tumor Presenting as a Mixed Cryoglobulinemic Vasculitis - Gabriel Cojuc-Konigsberg; Isabel Natera-Comte; Blanca E. López Graciano; Luis Gerardo Mosqueda López; José Alonso Ávila-Rojo; Braulio Martínez; Juan C. Ramírez-Sandoval (Case Reports in Oncological Medicine)
Background. Mixed cryoglobulinemia syndrome (MCS) is a rare entity with a variety of causes but has not been associated with testicular germ cell tumors. We present here a case of a patient with a nonseminomatous germ cell tumor (NSGCT) presenting as a type III mixed cryoglobulinemic vasculitis. Case Presentation. A 58-year-old male exhibited typical clinical features of vasculitis, including weakness, fatigue, palpable purpura, multiple mononeuropathy, and a low C4 level. An MCS diagnosis was confirmed by the presence of cryoglobulins (6%) with polyclonal IgM and IgG components and biopsy proven leukocytoclastic vasculitis. Concomitantly, a stage IIIC (TxNxM1bS1) germ tumor with marked elevation of serum beta-human chorionic gonadotropin (2764 mUI/mL) was diagnosed. An aggressive treatment was needed, including methylprednisolone pulses, plasmapheresis, rituximab, followed by orchiectomy, and chemotherapy (bleomycin/etoposide/cisplatin). After tumor resection and treatment, cryoglobulins decrease to 0%, suggesting a paraneoplastic origin of the vasculitis. Conclusion. To the best of our knowledge, this is the first case of MCS possibly attributable to a NSGCT. This case further elaborates on the presentation of mixed cryoglobulinemia vasculitis and adds to the published literature on the topic.